2018
DOI: 10.1177/1077559518816877
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of In Situ Training for Disclosure as a Standalone and a Booster to a Child Protective Behaviors Education Program

Abstract: In this study, the effectiveness of the Observed Protective Behaviors behaviors test, a single-session, disclosure-focused, in situ skills training (IST), was evaluated as a standalone program (IST only) or as a booster to the child protective education program, Learn to be safe with Emmy and friends ™ (program + IST). Participants included 281 Year 1 children (5–7 years; 52% male), randomly assigned to IST only, program + IST, program only or waitlist, and followed across 6 months. At each assessment, childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Children with parents in the control group were 16.5% more likely than those whose parents received the SSI to have anxiety disorders at one-year follow-up; further, parents rated the SSI as highly acceptable. Another SSI focusing on "in situ skills training" (IST) was tested as a standalone intervention and as an adjunct to a 5-week, school-based program promoting risk disclosure among foster care-involved youth (White et al, 2019). The IST-only condition significantly increased children's disclosure intentions, but not symptoms of anxiety (d = 0.11), relative to a waiting-list control.…”
Section: Therapist Administered Ssis Since 2016mentioning
confidence: 99%
“…Children with parents in the control group were 16.5% more likely than those whose parents received the SSI to have anxiety disorders at one-year follow-up; further, parents rated the SSI as highly acceptable. Another SSI focusing on "in situ skills training" (IST) was tested as a standalone intervention and as an adjunct to a 5-week, school-based program promoting risk disclosure among foster care-involved youth (White et al, 2019). The IST-only condition significantly increased children's disclosure intentions, but not symptoms of anxiety (d = 0.11), relative to a waiting-list control.…”
Section: Therapist Administered Ssis Since 2016mentioning
confidence: 99%
“…However, changes to students' intention to disclose abuse did not significantly increase. Unfortunately, additional randomised control trials were not conducted to evaluate the efficacy of any one of these programmes to reduce cyber abuse, revealing a clear research gap (see Diaz et al, 2021;Kenny et al, 2022;Nyberg et al, 2021;Solehati et al, 2022;White et al, 2019).…”
Section: Police-led Programmes To Reduce Cyber Abuse In Schoolsmentioning
confidence: 99%
“…On the other hand, SST is not a treatment modality that easily enables the measurement of change over several time points ( 36 ). Although there is a growing effort and evidence to demonstrate clinically significant improvement over time with controlled studies ( 17 , 37 , 38 ), most of them showed short-term improvement only after 1 month and failed to demonstrate improvement in further follow-ups ( 39 , 40 ). Other outcome instruments for psychotherapy are designed for monitoring, where a course of therapy is assumed, which does not match with the immediacy of the SST framework, where using a series of scores to monitor change is not expected or instruments that ask temporal questions about problems (e.g., “ …in the last two weeks ”) such as the YP-CORE and CORE ( 41 ) may be inadequate to assess the here and now.…”
Section: Introductionmentioning
confidence: 99%